2017
DOI: 10.3390/mi8070209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Diffusion Process by pH Indicator in Microfluidic Chips for Liposome Production

Abstract: In recent years, the development of nano- and micro-particles has attracted considerable interest from researchers and enterprises, because of the potential utility of such particles as drug delivery vehicles. Amongst the different techniques employed for the production of nanoparticles, microfluidic-based methods have proven to be the most effective for controlling particle size and dispersity, and for achieving high encapsulation efficiency of bioactive compounds. In this study, we specifically focus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…30 For the experimental evaluation of mixing performance, a variety of microscopic techniques with the aid of ow visualisation by pH-sensitive, coloured and uorescent dyes, have been employed. 14,31,32 Two-dimensional projection of a 3D droplet into a plane has been addressed by Fluorescence-Lifetime Imaging (FLIM) providing three-dimensional information about a tracer distribution for both, quasi-steady ows 32 and rapidly owing droplets. 33 However, a high purchasing cost signicantly hinders the widespread application of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…30 For the experimental evaluation of mixing performance, a variety of microscopic techniques with the aid of ow visualisation by pH-sensitive, coloured and uorescent dyes, have been employed. 14,31,32 Two-dimensional projection of a 3D droplet into a plane has been addressed by Fluorescence-Lifetime Imaging (FLIM) providing three-dimensional information about a tracer distribution for both, quasi-steady ows 32 and rapidly owing droplets. 33 However, a high purchasing cost signicantly hinders the widespread application of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Solvent and no-solvent diffusion by hydrodynamic flow focusing was monitored by an adaption of a previous published methodology [32]. Briefly, a change in colour of a pH indicator dye (bromoxylenol blue) was used, since this dye exhibits a strong yellowish colour at pH below 6.0 and blue at pH above 7.6.…”
Section: Mixing Efficiency Visualizationmentioning
confidence: 99%
“…Some authors [19,20,32] reported a significantly increase in PDI with the increment of FRR for an identical chip configuration, but for liposomes production instead. However, our observation was in line with that of Bottaro et al [32] in a "Y"-shaped device, while Joshi et al [21] described also a reduction in PDI as FRR increase during liposome formation. No significant differences on PDI were observed for all Q T levels applied.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives to such types of devices are Dean forces-based micromixers, which use curvilinear paths to induce centripetal forces, thus speeding up the mixing process [20][21][22]. Multiple micromixer designs using Dean forces have been previously proposed [19,[23][24][25][26][27], showing promising results for lipid-based nanoparticles both in terms of increased yield (by reducing the Flow Rate Ratio (FRR) required to produce nanosized particles) as well as ease of fabrication of the microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%